Annual Direct Economic Burden and Influencing Factors of Dry Eye Diseases in Central China. (4th March 2023) - Luo, Yanzhu; Yang, Wanju; Qi, Mengying; Wang, Yuhong; Li, Shaowei; Wang, Mingwu; Zeng, Qingyan
ABSTRACT: Purpose: To study the direct economic burden of dry eye diseases (DED) on Chinese residents and analyze the influencing factors of the direct economic burden of patients with DED. Methods: Two hundred and twenty-one Chinese adults with DED who underwent treatment in Wuhan Aier Hankou Eye Hospital were enrolled in this health economics research from January 2018 to August 2018 and followed for at least 1 year. Examination, pharmacological therapy, and nonpharmacological therapy costs were collected to calculate the annual direct economic burden of DED on patients through the outpatient medical record system. Results: Annual direct economic burden caused by DED on each patient was 465.54 ± 303.08. The direct economic burden of female patients in the 40–49 years group was significantly higher than that of male patients ( P < .05). Age, number of hospital visits and severity of DED were showed a significant influence on the direct economic burden both in univariate linear regression analysis and multiple linear regression analysis. Subtype of DED was showed a significant influence on the direct economic burden in multiple linear regression analysis after eliminating confounding factors. Conclusion: This study preliminarily analyzed the direct economic burden of Chinese DED patients. Age, number of hospital visits, severity of DED, mixed and evaporative dry eye (EDE) subtypes are shown to be the significant influencing factors of the direct economic burden and sex is a potential influencing factor.